(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to examine the impact of transformational leadership on organizational agility among employees at the Social Security Fund – East Benghazi branch. A descriptive-analytical method was employed, and primary data were collected using a questionnaire developed by the researcher based on previous studies. The study sample consisted of 47 employees, selected through simple random sampling. Statistical analyses indicated that both transformational leadership and organizational agility levels were high among the employees. Furthermore, transformational leadership was found to have a statistically significant effect on organizational agility (α ≤ 0.05). The findings highlight the substantial role of transformational leadership in enhancing organizational agility, particularly through its dimensions of intellectual stimulation and inspirational motivation.